Bibliometric analysis of climate change research: Education in water use - E. M. Barturen Mondragón; G. A. Quezada Castro; M. del P. Quezada Castro; M. del P. Castro Arellano (Образование и наука)
Introduction. The population has the right to receive information about the resources it consumes. Given the increase in environmental pollution, there is a need to educate everyone about the use of water. This will make it possible to demand its quality and contribute to the adaptation caused by climate change.Aim. The study aims to carry out a bibliometric analysis of water use in the context of climate change.Methodology and research methods. The PRISMA method was used for this study. The Scopus database was selected because of its multidisciplinary nature. The search term was checked against the UNESCO Thesaurus. The data were analysed using the R-studio software and the Biblioshiny interface.Results. A total of 1738 documents were analysed and it was verified that the research topic quadrupled its scientific production since 2012. It was found that the highest scientific production is 18 documents per author; with Swiss journals located in Scopus Q1 are the most prominent and prioritising the research topic. It also highlights that the common themes of the papers are water supply, water use efficiency, and water management. In the same vein, the conclusion is that it is necessary to question the unjustified use of water; otherwise, the resource could disappear.Practical significance. This study demonstrates the need for the population to learn the meaning of responsible water use, which is why it is recommended that education on water use be implemented to counteract the effects of climate change.